Інтеграція українського суспільства в контексті викликів та загроз подій на Донбасі - Заблодська, Інна Володимирівна; Попова, Ірина Анатоліївна; Рогозян, Юлія Сергіївна; Мартинович, Наталія Олександрівна; Перепелюкова, Олена Василівна (Східноукраїнський національний університет імені Володимира Даля, 2015)
Стаття призвана частково відповісти на актуальні питання, пов’язані з викликами та загрозами подій на Донбасі. Авторами досліджено питання щодо соціально-економічних втрат країни, обумовленими подіями на сході, соціально-економічний потенціал вимушених переселенців. Проаналізовано ризики та загрози подальшому розвитку України, виявлено нові можливості для розбудови сучасної національної економіки. Також у статті визначено складові політики інтеграції українського суспільства в контексті проблеми на сході країни.

Article has been made to partially answer the urgent questions related to the challenges and threats of events in Donbass. The authors investigated the issue of socio-economic losses the country, due to events in the east, socio-economic potential of IDPs. Analysis of risks and threats to further development of Ukraine is already done, found new opportunities for building a modern national economy. Also in the article the integration policy components of Ukrainian society in the context of the east were considered. The problems of the forced relocation of many hundreds of thousands and millions people belong to the most pressing problems of the modern world, as involuntarily displaced people as a result of military, political and other conflicts, as defined by the UN, is one of the most vulnerable population, so this theme is relevant in Ukrainian present.
Keywords: інтеграція; українське суспільство; події на Донбасі; соціально-економічний розвиток; ризики; можливості; production infrastructure; production capacity; transport infrastructure; social infrastructure; the cost of destruction; assessment of losses; losses